Badania Eksperymentalne Kul Grubościennych Obciążonych Hydrostatycznym Ciśnieniem Zewnętrznym - Z. Wesołowski (Engineering Transactions, 1963)
This paper presents the results of stability tests of thick-walled spheres loaded by external pressure. The measurements have been performed using spheres with outer radius 39.5 mm and wall thickness up to 7.8 mm made of soft rubber. On the basis of the experimental data obtained, the critical pressure and strain is obtained for three different wall-thicknesses as well as for these quantities.